A Case of HIV (Human Immunodeficiency Virus) Infected Child Born to HIV Positive Mother - Corry S. Matondang; Siti D. Wisnuwardhani; Rulina Suradi; Hindra I. Satari; Graham RR; Sjawitri P. Siregar; Arwin A.P. Akib; Zakiudin Munasir (Indonesian Pediatric Society, 1997)
A case of HIV infected Indonesian baby girl bom from an HIV positive mother is reported. This is the first HIV infected child reported in Indonesia. The diagnosis was based on the positive DNA HIV and HIV culture in the baby's blood taken at 3 days old. At this time the baby is still asymptomatic. Despite this we gave her prophylactic treatment against Pneumocystis Carinii infection to prevent the possibility of Pneumocystis Carinii Pneumonia which is usually fatal under 1 year old. The positive HIV at 3 days old may indicative of intrauterine nans mission. Because she is still asymptomatic, the intrauterine infection may be occured during late gestation. In spite of this we hope that the HIV- infection in this baby is not a progressive one.